Right hip gonococcal septic arthritis treatment with successful transition to oral fluoroquinolone. Issue 9 (16th September 2022) - Kiamos, Amy; Torrente, Natalie; Sands, Michael; Verdecia, Jorge
Abstract : We present a case of gonococcal septic arthritis of the right hip diagnosed via synovial fluid cultures. Antimicrobial susceptibility testing of the synovial fluid demonstrated susceptibility to tetracycline, ciprofloxacin, cefixime and ceftriaxone. Our patient was initially treated with ceftriaxone and was successfully de-escalated to oral levofloxacin to complete the treatment. This case is interesting given the rarity of disseminated gonococcal infections in the 21st century and that most clinical isolates of Neisseria gonorrhoeae are increasingly resistant to fluoroquinolones.